TRAUMA MASA LALU DAN PEMBENTUKAN PANDANGAN HIDUP TOKOH UTAMA DALAM NOVEL SEPORSI MIE AYAM SEBELUM MATI: KAJIAN PSIKOLOGI SASTRA SIGMUND FREUD - Syafrina Yasifa Putri; Elsa Mulya Karlina (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This research investigates how past traumatic experiences contribute to shaping the protagonist's life outlook in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna, applying Sigmund Freud's literary psychology framework as its analytical lens. The study is motivated by the recognition that unresolved psychological wounds often influence how a person interprets the self, others, and life in general, as illustrated through the character Ale, who endures childhood bullying, rejection by his social environment, and prolonged loneliness that gradually pushes him toward deep despair. To explore this issue, the research adopts a qualitative method in the form of library research. The novel Seporsi Mie Ayam Sebelum Mati (2025) serves as the principal data source, supported by relevant books, academic journals, and earlier related studies functioning as secondary data. Data were gathered through a combination of close reading, careful observation, and systematic note-taking, then processed using the Miles and Huberman analytical model, which involves data reduction, data presentation, and conclusion verification. Key elements of Freud's psychoanalytic theory namely the id, ego, superego, the unconscious mind, and defense mechanisms are employed to trace the connection between the protagonist's past trauma and the formation of his worldview. The results of this study are expected to enrich theoretical perspectives within literary psychology and provide practical value for teachers, students, educational institutions, and future researchers interested in applying similar approaches to the appreciation of literary works.